Sperm DNA damage and seminal oxidative status after shock-wave lithotripsy for distal ureteral stones - KOÇYİĞİT, ABDÜRRAHİM; Gulum, Mehmet; Yeni, Ercan; Kocyigit, ABDÜRRAHİM; Taskin, Abdullah; Savas, Murat; Ciftci, Halil; Altunkol, Adem (My University, 2011)
Objective: To investigate the relationship between level of sperm DNA damage, seminal oxidative status, and shock-wave lithotripsy (SWL) for distal ureteral stones.